Pediatric endocarditis - a stone left after the pandemic cascade - Lupu, Ancuta; Nedelcu, Alin Horatiu; Budescu, Paula Diana; Jechel, Elena; Starcea, Iuliana Magdalena; Frasinariu, Otilia Elena; Ioniuc, Ileana; Badescu, Minerva Codruta; Salaru, Delia Lidia; Munteanu, Dragos; Russu, Ruxandra; Sascau, Radu Andy; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Infective endocarditis is a rare disease in children. The etiology is mainly bacterial. However, viral infective endocarditis, possibly related to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has also been reported. The pathophysiological principle of the connection between the two entities seems to be attributed to the transient immune deficiency of the body during the infection. Additionally, SARS-CoV-2 is reported in the literature as a direct cardiopathic virus. Therefore, the new coronavirus seems to have the ability to affect both the intact cardiac tissue and the previously damaged one both during the acute episode and at a distance from it. Consequently, we propose to review the main pathophysiological aspects of pediatric cardiac damage caused by SARS-CoV-2. The ultimate goal is to deepen existing knowledge, broaden the horizon of understanding and analysis regarding the systemic damage induced by viral infections, and strengthen an information base from which to start a meta-analysis. Next, we performed a non-systematized screening of the specialized literature with reference to cases of endocarditis in the pediatric population, reported in the period 2020–2023. From the total of articles found, we chose to include in the review a number of 6 case reports, including a number of 7 patients (5 children and 2 adolescents). Analysis of reports suggests that SARS-CoV-2 infection could play a role in the development of endocarditis, either directly through active infection or indirectly through a post-infectious immune response. Also, pre-existing conditions and complex medical history predispose to an increased risk of developing a severe, complicated form of endocarditis. Also, the lack of data on the vaccination history and the failure to categorize the infection depending on the type of antibodies (IgM or IgG) in some studies represent a major bias in the reports. The latter make it difficult to evaluate the influence of vaccination and the impact of acute versus chronic infection on the course of cases.